443 Arterial hypertension in aortic valve stenosis: a critical update. (8th December 2021) - Basile, Christian; Fucile, Ilaria; Manzi, Maria Virginia; Ilardi, Federica; Franzone, Anna; Mancusi, Costantino
Abstract: Aims: Aortic stenosis (AS) is a very common valve disease and is associated with high mortality once it becomes symptomatic. Arterial hypertension (HT) has a high prevalence among patients with AS leading to worst left ventricle remodelling and faster degeneration of the valve. HT also seems to interfere with the assessment of the severity of AS leading to an underestimation of the real degree of stenosis. Treatment of HT in AS has historically been associated with reluctance due to both the lack of clear guidelines and the fear of adverse effects, but the most recent evidence shows as several drugs that can be used. Methods: The pathophysiology of the combination of AS and HT is the association of a first fixed mechanical obstruction of the aortic root and a second obstruction due to systemic vascular resistance. Consequently, a decrease in systemic vascular resistance through, for example, the administration of vasodilators could theoretically cause a drop in systemic pressure due to the fixed mechanical obstruction given by the stenosis which prevents an increase in cardiac output. This theory was the basis for avoiding vasodilators in patients with AS. Results: There is a unanimous opinion on maintaining blood pressure values of 130–139 mmHg of systolic and 70–90 mmHg of diastolic, but there is not the same agreement on which drugs to adopt to achieve the aforementioned values. Renin-Angiotensin-Aldosterone system inhibitors are certainly the first-line treatment thanks to their cardioprotective, plaque stabilizing, and antiarrhythmic effect since they are also associated with increased survival rates and greater left ventricular mass reduction in patients after surgical or transcatheter aortic valve replacement for severe AS. If blood pressure is not yet controlled, the addition of a beta-blocker should be considered: metoprolol has the greatest literature, showing not only an improvement in haemodynamic and metabolic performance but also a reduction in mortality in patients who already presented with coronary artery disease. Mineralocorticoid receptor antagonist can be used, among them eplerenone has been studied and can be useful to relieve symptoms of patients with a flare-up of heart failure by reducing the preload, provided that a close fluid and echocardiographic monitoring is implemented. Conclusions: The use of phosphodiesterase 5 inhibitors can improve the haemodynamic status of patients with aortic stenosis and reduce the level of left ventricular hypertrophy, as well as improve pulmonary circulation and exercise tolerability of patients with AS, however it should be considered that in other studies sildenafil was associated with a worse clinical outcome. Calcium channel blocker are one the most used medications in patients with HT, but their use was associated with a 7-fold relative risk of all-cause mortality independent of known confounders and was also associated with an adverse effect on treadmill exercise and higher risk of all-cause mortality in patients with AS.